Korean Drama and Popular Culture on Youth in RCTI From a Cultivation Theory Perspective - Heny Rahmawati (UMSU, 2023)
The Korean drama film business is in high demand worldwide, particularly among women. This community enthusiasm will affect the tourism industry by increasing the number of international tourists visiting Korea and increasing the popularity and distribution of Korean-style technology, food, apparel, and other products. In the eyes of the world, the country's reputation is improving; they have succeeded in disseminating their identity through popular culture. This study seeks to determine how K-Drama, a product of South Korean popular culture, has contributed to the growth of the Korean Wave in Indonesia. The data were collected using a qualitative study approach to describe Korean pop culture's impact on Indonesian society's routines. In this study, the interpretivism research paradigm was utilized. Purposive sampling technique Purposeful sampling, often known as an assessment or expert sample, is a non-probability sample type. Given the substantial support from the government, the conclusion reached is that Korean pop culture has the potential to dominate global entertainment.